RETRACTED: Human development as one of the factors of the transition to the knowledge economy - Bimagambetova Zhibek T.; Murtaza Alma Sh.; Nurgalieva Mayra N.; Tovma Nataliya A.; Mishenko I.; Tleppayev Arsen (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001